Pendekatan Gender dalam Studi Quran - Asna Andriani (Institut Pesantren KH Abdul Chalim Mojokerto, 2017)
The Qur'an as a sacred Muslim scripture of justice that upholds the principle of equality (egalitas)between men and women, but in its interpretation there are some points that seem to discreditwomen, resulting in a gender-biased understanding. This invites question marks among Muslimsitself. Is there a mistake lies in the text of the Qur'an or on how to understand it? Is it possiblethat Islam that teaches the principle of equality contains contradictory things, such asunderestimating women? So to reveal the crucial issues that invite the interpretation of thegender-biased verses of the Qur'an, a special study is needed about the egalitarian interpretiveparadigm and not contaminated by the patriarchal culture. This paper attempts to reveal theparadigm of interpretation in the study of the Qur'an with the gender approach used by feminists,in order to gain an understanding and interpretation of the verses of the Qur'an that fit thecontexts and demands of times.